Risky behavior among Chilean youths; Conductas de riesgo entre los jóvenes en Chile - Rafael Novella; Andrea Repetto (Estudios de Economía, 2024)
This paper examines the connection between risky behaviors and various so-cioeconomic factors, including skills, preferences, aspirations, expectations, and exposure to shocks. Using a representative sample of Chilean youths aged 15 to 19 years old, our analysis identifies self-esteem, risk aversion, and edu-cational aspirations as relevant factors associated with participation in risky activities. Remarkably, even after accounting for socio-demographic factors, skills, expectations, aspirations, and preferences, we uncover a significant cor-relation between exposure to shocks at both individual and family levels and engagement in risky behavior. Particularly striking is the association between experiencing job loss and family illness and the prevalence of risky behaviors. Additionally, we observe positive correlations among the unexplained vari-ability of these behaviors, suggesting a complementary relationship between these activities. While these patterns are correlational rather than causal, they offer valuable insights into the determinants of risky decision-making among youths.
Keywords: D91; I12; I31; 330; Smoking; alcohol; violence; unemployment; health; self-esteem